Neuregulin 1 Drives Morphological and Phenotypical Changes in C2C12 Myotubes: Towards De Novo Formation of Intrafusal Fibres In Vitro - Barrett, Philip; Quick, Tom J.; Mudera, Vivek; Player, Darren J. (Frontiers in Cell and Developmental Biology, 2022)
Muscle spindles are sensory organs that detect and mediate both static and dynamic muscle stretch and monitor muscle position, through a specialised cell population, termed intrafusal fibres. It is these fibres that provide a key contribution to proprioception and muscle spindle dysfunction is associated with multiple neuromuscular diseases, aging and nerve injuries. To date, there are few publications focussed on de novo generation and characterisation of intrafusal muscle fibres in vitro. To this end, current models of skeletal muscle focus on extrafusal fibres and lack an appreciation for the afferent functions of the muscle spindle. The goal of this study was to produce and define intrafusal bag and chain myotubes from differentiated C2C12 myoblasts, utilising the addition of the developmentally associated protein, Neuregulin 1 (Nrg-1). Intrafusal bag myotubes have a fusiform shape and were assigned using statistical morphological parameters. The model was further validated using immunofluorescent microscopy and western blot analysis, directed against an extensive list of putative intrafusal specific markers, as identified in vivo. The addition of Nrg-1 treatment resulted in a 5-fold increase in intrafusal bag myotubes (as assessed by morphology) and increased protein and gene expression of the intrafusal specific transcription factor, Egr3. Surprisingly, Nrg-1 treated myotubes had significantly reduced gene and protein expression of many intrafusal specific markers and showed no specificity towards intrafusal bag morphology. Another novel finding highlights a proliferative effect for Nrg-1 during the serum starvation-initiated differentiation phase, leading to increased nuclei counts, paired with less myotube area per myonuclei. Therefore, despite no clear collective evidence for specific intrafusal development, Nrg-1 treated myotubes share two inherent characteristics of intrafusal fibres, which contain increased satellite cell numbers and smaller myonuclear domains compared with their extrafusal neighbours. This research represents a minimalistic, monocellular C2C12 model for progression towards de novo intrafusal skeletal muscle generation, with the most extensive characterisation to date. Integration of intrafusal myotubes, characteristic of native, in vivo intrafusal skeletal muscle into future biomimetic tissue engineered models could provide platforms for developmental or disease state studies, pre-clinical screening, or clinical applications.